Toward an Islamic Functional Theory of Marital Assets: Bridging Classical Fiqh and Modern Legal Needs - Suprihatin, Suprihatin; Lawang, Karimuddin Abdullah; Rusyana, Ayi Yunus; Najmudin, Nandang (Hukum Keluarga Islam IAIN LANGSA, 2025)
This study originates from the absence of a functional theory that systematically explains the legal status of joint marital property within the framework of Islamic law. Previous studies have predominantly focused on normative aspects such as shirkah (partnership), maintenance (nafaqah), and hibah (gifts), without conceptualizing joint property as an instrument for protecting the reciprocal rights of spouses. This theoretical gap raises critical questions regarding how Islamic jurisprudence can respond to the demands of modern legal systems that emphasize legal certainty, economic justice, and mutual protection within marriage. Accordingly, this research aims to formulate a Functional Theory of Joint Marital Property from an Islamic perspective through the integration of classical fiqh principles, social functionalist theory, and the local wisdom of the Indonesian archipelago (Nusantara). The study employs a library-based research method with normative analysis, utilizing approaches from usul al-fiqh, legal hermeneutics, and social systems theory. This multidimensional approach enables the identification of principles of reciprocity, public interest (maslahah), and rights protection embedded in classical fiqh texts, as well as their relevance to the Indonesian legal system. The findings indicate that joint marital property serves three primary functions: a protective function safeguarding the rights of both spouses; a stabilizing function ensuring the continuity and resilience of the household; and an integrative function that harmonizes Islamic jurisprudence with the requirements of modern legal frameworks. This functional theory of joint marital property constitutes a novel contribution to the development of Islamic family law in Indonesia and may serve as a foundational framework for regulatory reform, the formulation of jurisprudential guidelines, and the strengthening of rights-based protection mechanisms within marriage.